Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation of Recurring Issues from a Decade of Evaluation-Lessons for the IMF. (Policy Papers; Policy Paper ;, 2015)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) evaluation of Recurring Issues from a Decade of Evaluation: Lessons for the IMF.